2010
DOI: 10.1007/s10529-010-0346-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutanase from Paenibacillus sp. MP-1 produced inductively by fungal α-1,3-glucan and its potential for the degradation of mutan and Streptococcus mutans biofilm

Abstract: Laetiporus sulphureus is a source of α-1,3-glucan that can substitute for the commercially-unavailable streptococcal mutan used to induce microbial mutanases. The water-insoluble fraction of its fruiting bodies from 0.15 to 0.2% (w/v) induced mutanase activity in Paenibacillus sp. MP-1 at 0.35 μ ml−1. The mutanase extensively hydrolyzed streptococcal mutan, giving 23% of saccharification, and 83% of solubilization of glucan after 6 h. It also degraded α-1,3-polymers of biofilms, formed in vitro by Streptococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 14 publications
3
44
0
1
Order By: Relevance
“…The pH dependence of a-1,3-glucanase HF65 activity was almost similar to those of bacterial a-1,3-glucanases that have been reported to exhibit optimum activity at acidic pH regions (Fuglsang et al, 2000;Imai et al, 1977;Meyer and Phaff, 1980;Pleszczy¢ nska et al, 2010;Shimotsuura et al, 2008;Suyotha et al, 2014;Tsumori et al, 2011). The effect of temperature was also investigated in the range 30-80∞C (Fig.…”
Section: Fig 1 Sds-pagesupporting
confidence: 68%
See 2 more Smart Citations
“…The pH dependence of a-1,3-glucanase HF65 activity was almost similar to those of bacterial a-1,3-glucanases that have been reported to exhibit optimum activity at acidic pH regions (Fuglsang et al, 2000;Imai et al, 1977;Meyer and Phaff, 1980;Pleszczy¢ nska et al, 2010;Shimotsuura et al, 2008;Suyotha et al, 2014;Tsumori et al, 2011). The effect of temperature was also investigated in the range 30-80∞C (Fig.…”
Section: Fig 1 Sds-pagesupporting
confidence: 68%
“…Thus, the enzyme is of interest due to its potential use in the removal of dental plaque and the biological control of pathogenic fungi. Some studies have demonstrated the ability of a-1,3-glucanases to reduce the plaque synthesized by Streptococcus species, as well as to inhibit plaque formation (Fuglsang et al, 2000;Pleszczy¢ nska et al, 2010;Shimotsuura et al, 2008;Tsumori et al, 2011;Wiater et al, 2004Wiater et al, , 2008. Moreover, they indicated that the degradation of plaque by the enzyme was more effectively performed in combination with dextranase (Fuglsang et al, 2000;Shimotsuura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-1,6-glucose linkage로 구성된 덱스트란(dextran), -1,6-glucose linkage가 주된 결합인 수용성 글루칸 (water-soluble -glucan), 그리고 -1,3-glucose linkage가 주된 결합인 비수용성 글루칸(water-insoluble -glucan), 즉 mutan (뮤탄)으로 구분된다 6) . …”
Section: 5)unclassified
“…Type 71 -1,3-glucanases have been found in fungi, such as Trichoderma, 3) Penicillium, 3) Aspergillus, 4) and Schizosaccharomyces, 5) and type 87 enzymes have been found in Bacillus 6) and Paenibacillus. 7) These enzymes have been investigated not only to determine their physiological roles in these organisms, 4,5) but also for application in degrading dental plaques, 8,9) controlling pathogenic fungi, 10) preparing fungal protoplasts, 11) and for other uses.…”
mentioning
confidence: 99%